Vocabulary integration environment: vine (2007)
Interoperability between distributed information systems requires an agreement of metadata standards, protocols, interfaces and controlled vocabularies. Such an agreement is often pursued by adopting standards published by organizations such as the International Organization for Standardization (ISO) and the Open Geospatial Consortium (OGC). These standards are general and do not fully dictate the control vocabularies used for annotating metadata. Therefore, when communities share metadata they encounter semantic conflicts because of the â€œstageâ€, â€œgage heightâ€ and â€œwater elevationâ€ are different concepts that are semantically equivalent. To be able to solve these semantic heterogeneities, VINE, the Vocabulary Integration Environment tool, was created. This tool was successfully used at the workshop â€œAdvancing Domain Vocabulariesâ€, hosted by the Marine Metadata Initiative (MMI) in 2005. This tool specializes in â€œthesauri typeâ€ relations to map controlled vocabularies, encoded as (Resource Description Framework) RDF graphs. VINE also allows free text searches in the graph. It is a JAVA Eclipse Plugin and it follows the Model View Controller paradigm. The architecture of the tool and the concept of the smart deep graph search will be discussed.